2015
DOI: 10.7566/jpsj.84.094702
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz Transitions in Magnetic Phases of the Periodic Anderson Model

Abstract: We investigate the reconstruction of a Fermi surface, which is called a Lifshitz transition, in magnetically ordered phases of the periodic Anderson model on a square lattice with a finite Coulomb interaction between f electrons. We apply the variational Monte Carlo method to the model by using the Gutzwiller wavefunctions for the paramagnetic, antiferromagnetic, ferromagnetic, and charge-density-wave states. We find that an antiferromagnetic phase is realized around half-filling and a ferromagnetic phase is r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…It was found previously [47,48] that for the antiferromagnetic phases, bond fermion theory agrees well with numerical results for the 2D KLM. More precisely, the quite intricate phase diagram in the (J/t, n c ) plane obtained from bond Fermion theory agrees qualitatively with that from VMC [26,27,29] and DMFT [30], the quasiparticle band structure for the antiferromagnetic phase of the Kondo insulator -i.e. the KLM for n e = 2 -and its change with J agree in considerable detail with that from DCA [32].…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…It was found previously [47,48] that for the antiferromagnetic phases, bond fermion theory agrees well with numerical results for the 2D KLM. More precisely, the quite intricate phase diagram in the (J/t, n c ) plane obtained from bond Fermion theory agrees qualitatively with that from VMC [26,27,29] and DMFT [30], the quasiparticle band structure for the antiferromagnetic phase of the Kondo insulator -i.e. the KLM for n e = 2 -and its change with J agree in considerable detail with that from DCA [32].…”
Section: Introductionsupporting
confidence: 75%
“…The KLM has been discussed frequently by using the mean-field (or saddle-point) approximation, where the exchange term which is quartic in electron operators is mean-field factorized [7][8][9][10][11][12][13][14][15][16][17]. There have also been many numerical studies using density matrix renormalization group calculations [18][19][20][21][22], quantum Monte-Carlo [23], series expansion [24,25] variational Monte-Carlo (VMC) [26][27][28][29] Dynamical Mean Field Theory (DMFT) [30] or Dynamical Cluster Approximation (DCA) [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above theories assumed the paramagnetic (PM) state; however, within the GWF, it has also been revealed that the PM state is unstable against magnetic order in the parameter region where the heavy-fermion state is realized. 1,3,[5][6][7][8][9][10][11] To overcome this difficulty, we should improve the variational wavefunction. For this purpose, it is useful to consult the literature on other multiorbital systems since the periodic Anderson model is also a multiorbital system with the conduction band and f orbital.…”
mentioning
confidence: 99%
“…One is the GWF, which has been used to study this model, for example, by the variational Monte Carlo method as in this study. 2,8,9,11 For U → ∞, the Gutzwiller parameter is zero, and the GWF is given by…”
mentioning
confidence: 99%